Suicide rates between men and women in Brazil, 2000-2017 - Danielly Cristina de Andrade Palma; Beatriz Fátima Alves de Oliveira; Eliane Ignotti (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2021)
Abstract: This study aimed to analyze the trend in the standardized suicide rates by gender, according to Brazil's geographic regions from 2000 to 2017. Mortality data were retrieved from the Brazilian Mortality Information System database. Linear regression models were used, and Durbin-Watson tests were applied to detect the independence of the residues, as well as Prais-Winsten to control serial autocorrelation. We classified the trends as increasing, decreasing, and stable at 5% significance level. The standardized rate of deaths by suicide for men increased by 75%, from 6.5 to 11.3 deaths per 100,000 inhabitants. For women, the increase was 85%, from 1.6 to 3.0 deaths per 100,000 inhabitants. We found a gradual increase in the standardized suicide rates in all regions for both genders. The growth magnitude of suicide rates in the South is twice for women, whereas for the Northeast it is greater for men. The South and the Central-West regions presented the highest rates, whereas the North the lowest. The trend of standardized rates of suicide is linear and significantly increasing for Brazil and its total geographic regions for both genders. Male and female suicide rates indicate different risk rates according to gender.